PENGARUH KOMPETENSI, MOTIVASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT. BPR ASHI SEMPIDI, BADUNG - Ni Made Yunita Sari; Ida Bagus Widiadnya; Sapta Rini Widyawati (VALUES, 2022)
The purpose of this study was to determine the effect of competence, motivation and organizational commitment on employee performance at PT. BPR Ashi Sempidi Badung. The population and samples taken were 30 respondents, with the method of determining the sample using the Slovin formula. Data was collected through questionnaires, documentation studies, observations and interviews. The analysis technique used is multiple linear regression analysis, analysis of determination and t test. The results showed that competence, motivation and organizational commitment partially have a positive and significant effect on employee performance at PT. BPR Ashi Sempidi Badung.